2014
DOI: 10.4103/2229-5178.131071
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ACTH test and estimation of a safe dose for high potency steroids in vitiligo: A prospective randomized study

Abstract: Background:Topical corticosteroids are used as first line of therapy for vitiligo, although side effects such as adrenal insufficiency are possible.Objectives:To establish the role of ACTH test before, during, and after treatment with high potency topical steroids; to determine if adrenal insufficiency occurs secondary to the use of high potency topical steroids in patients with vitiligo and intact cutaneous barrier; and also to determine response to treatment and side effects.Materials and Methods:Forty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Topical corticosteroids have been observed as effective in recent and facial lesions; however, to reduce the risk of side effects the administration should be limited to small areas, avoiding prolonged use and introducing another topical therapy after some weeks of continuous administration. [ 47 48 ]…”
Section: Treatments and Future Perspectivesmentioning
confidence: 99%
“…Topical corticosteroids have been observed as effective in recent and facial lesions; however, to reduce the risk of side effects the administration should be limited to small areas, avoiding prolonged use and introducing another topical therapy after some weeks of continuous administration. [ 47 48 ]…”
Section: Treatments and Future Perspectivesmentioning
confidence: 99%
“…The authors demonstrated that weekly use of 50 g (or less) of 0.05% clobetasol propionate cream for 12 weeks is safe, with no evidence of adrenal insufficiency, although local effects may occur. 15 To minimize the risk of side effects, topical corticosteroids should be limited to small areas, avoiding prolonged use on the face and flexures.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…The basic mechanism has not yet been clearly identified, however, various mechanisms have been proposed, including genetic association, 1,2 autoimmunity and oxidative stress, [3][4][5] neurohormonal imbalance, 6 abnormalities in the microenvironment surrounding the melanocytes [7][8][9] and intrinsic defects of melanocytes and periphery T cell regulator which promote innate immune attack. 10,11 Various modalities have been developed to treat vitiliginous skins, among others : a) anti-oxidant agents such as: Polypodium leucotomos as adjunct therapy with PUVA, 12 or fish oil 13 ; b) immunosuppressive agents such as: topical corticosteroid, 14 tacrolismus, [15][16][17] or calcipotriol, 18,19 either used as single modality or in combination with NB-UVB or excimer laser; c) UVA light combined with photosensitizer agent such as: psoralen, 20,21 ; d) oral minocycline 22,23 which nevertheless less effective than NB-UVB. 24 Previous study showed that minocycline could protect melanocytes from H 2 O 2 -induced cell death.…”
Section: Introductionmentioning
confidence: 99%